Balancing prescription with teacher and pupil agency: spaces for manoeuvre within a pedagogical model for working with adolescent girls. Issue 2 (3rd April 2018) - Kirk, D.; Lamb, C. A.; Oliver, K. L.; Ewing-Day, R.; Fleming, C.; Loch, A.; Smedley, V.
ABSTRACT: This paper explores the possibilities of using a pedagogical model for working with adolescent girls in physical education as a means of balancing the challenge of external prescription from outside the school with teacher and pupil agency. We report data from a study involving four schools in Glasgow. We note that the national curriculum for Scotland, Curriculum for Excellence, is a broad and bold type that provides teachers with 'spaces for manoeuvre' in order to shape local curricula that best meet the needs and interests of girls. This is particularly the case in physical education, which in the Basic General Education phase for 12–15 years olds there is no well‐established assessment regime. We identify four spaces for manoeuvre for teachers and pupils within an activist model: new forms of communication based on authorising pupil voice; offering choices and opening up learning possibilities; the co‐construction of a safe class environment; opportunities to rethink traditional structures based on the multi‐activity curriculum form. We conclude that an activist pedagogical model provided teachers and pupils with spaces to explore alternative practices to traditional forms of physical education.